OPTIMALISASI ATURAN PENERBITAN PASPOR BAGI CALON PEKERJA MIGRAN INDONESIA DI SEKTOR FORMAL(STUDI KASUS DI KANTOR IMIGRASI KELAS II TPI TANJUNG BALAI ASAHAN) - Erwin Syahputra; Dessy Indah Sari; Ica Zuniar Sari; Haris Fadila; M Robi Azhari; Johan Sitorus; Pamiluddin Pamiluddin; Anugerah Jaya Halawa; Arfi Yulian; Arina Rofiqoh Sitorus; Nadila Sirait; Bakti Bakti; Andrew Manasar; Roy Imanta Sembiring; Krisman Sitindaon; Andini Cahayani Sitorus; Cici Adelia; Erwin Zunaidi; Muhammad Anton; Edi Winardi; Abdul Hamid; Budianto Budianto (Nusantara Hasana Berdikari, 2022)
The high number of unemployed in the North Sumatra Province, specifically the City of Tanjung Balai Asahan and accompanied by the high demand for Indonesian Migrant Workers from countries that have a cooperation contract with the Indonesian state so that people are willing to become PMI with the aim of getting a better life. Types of Indonesian Migrant Workers in the formal sector which is classified into the type of Indonesian Migrant Workers who work for employers who are legal entities. The rules governing the requirements for issuing passports for prospective Indonesian migrant workers are regulated in the Regulation of the Minister of Law and Human Rights Number 8 of 2014 concerning Ordinary Passports and Travel Letters Like Passports. A recommendation letter for issuing a passport from the Manpower Office as one of the requirements for issuing passports for prospective Indonesian migrant workers, but in its implementation at the Immigration Office Class II TPI Tanjung Balai Asahan prospective Indonesian migrant workers, especially in the formal sector, often do not take care of issuing a recommendation letter for issuing passports from the Office Employment for various reasons. Therefore, it is explained the implementation of regulations for PMI candidates who register for passport issuance at the Immigration Office Class II TPI Tanjung Balai Asahan. Are the regulations for PMI candidates in the formal sector optimal? especially in the formal sector which is not yet optimal. This can be seen from the immigration system at the time of data entry, only prospective informal sector migrant workers are required to input PMI ID, while prospective Indonesian Migrant workers in the formal sector do not input PMI ID so that the data entry process can continue. So the urgency of the recommendation letter for passport issuance from the Manpower Office is only focused on prospective Indonesian migrant workers in the informal sector, not on prospective Indonesian migrant workers in the formal sector.